(untitled) (Вестник КазНУ. Серия Востоковедения, 2018)
This study reveals the cultural politics of the Post – Soviet Koreans in adaptation difficulty to the new state language – Kazakh. The Soviet Koreans were quickly assimilated into the Soviet language. Driving forces to assimilation were the strong external pressure with repression and violence under the Stalin regime, a breakthrough for survival and settlement, and at the same time voluntary willingness. However, since independence of Kazakhstan, the Koreans have not shown willingness to learn new state language. There was a boundary between the self-language and other language, which was reinforced and reproduced by the experiences and memories of the Soviet society. Moreover, the opening of economic activity to survive in a free market economy system has led to the passive attitude to the duties of state language, despite social pressure and discrimination in public sphere due to the language limit.